A Systematic Review of Food Hygiene Control in Food Service Providers: Review from 2000 - 2022 - Asnawi Othman, Khairil Anuar, Norazmir, (Pakistan Journal of Medical & Health Sciences, 2022)
From production through the intake, food hygiene particularly applies to the situations and processes that must be followed from production to consumption to guarantee the safety of the food produced. Food contamination may occur throughout the butchering or collecting, manufacturing, storage, distribution, transportation, and preparation processes. Food hygiene is described as “all circumstances and measures required throughout production, processing, storage, distribution, and preparation to guarantee the food is clean, healthy, and edible” Foodborne infections and even death can result from proper food hygiene. Around the world, contaminated food causes 600 million cases of foodborne disease and 420,000 deaths each year. Nearly 30% of all foodborne deaths worldwide occur in children under five. Campylobacter and norovirus are the main culprits found in most foodborne cases reported. Therefore, this research aims to assess food service providers' food hygiene knowledge, attitude, and practice at various phases of food supply. Moreover, this research also focused on different parts of the food supply chain, such as processing, manufacturing, and cooking. This review will also help develop stricter regulations and guidelines for food service providers to prevent more foodborne diseases. Keywords: food hygiene; foodborne diseases; food service providers; food handlers.